Relevansi Pemikiran Ekonomi Abu Ishaq Al-Syatibi Terhadap Dinamika Ekonomi Modern - Citra Annisa Ginting; Syawalia Arifa; Kia Napisa Siregar; Hasbi Rizky Rawy; Fitri Hayati M.A (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to examine the relevance of Abu Ishaq Al-Syatibi's economic thinking in the context of modern economic dynamics. By focusing on the principles of Maqasid alShariah, this article highlights the importance of protecting five basic aspects of human beings in fair, sustainable, and welfare-oriented economic development. This study uses a literature review method with a qualitative approach. The results of the study indicate that Al-Syatibi's principles are still relevant in responding to the challenges of globalization, social inequality, and the contemporary economic ethics crisis.